Determinants of Good Corporate Governance in the Banking Sector in Indonesia - Reschiwati; Daniza, Salsabila Firdausia Putri; Gusmiarni (Archives of Business Research, 2022)
This study aims to analyze the factors that influence good corporate governance in the banking sector in Indonesia. These factors are Corporate Culture, Board of Directors, Employee Performance, and Internal Audit as intervening variables. Respondents in this study were employees of Banks, both State-Owned Enterprises (BUMN) and private companies listed on the Indonesia Stock Exchange in 2020. The sample selection method was purposive sampling. Based on the established criteria, 10 banks in the Central Jakarta area were selected as samples. The data were analyzed by bootstrapping using smartPLS 3.0. software package. The results of this study indicate that corporate culture, board of directors, and employee performance have an effect on good corporate governance with internal audit as an intervening variable either partially or simultaneously. has been applied to assess how employee behavior influences the setting of company priorities. Meanwhile, the Board of Directors can improve the quality of company strategies, policies, and continue to carry out company management in accordance with the interests and objectives of the company. Employee performance can pay more attention to controlling behavior so that company management can be carried out openly and able to survive in competition with other companies in order to be able to survive in intense competition and in Good Corporate Governance can focus on basic values, namely paying attention in the physical form and behavior of employees. a company in order to create better company performance.